Modeling of a tubular-SOFC: the effect of the thermal radiation of fuel components and CO participating in the electrochemical process - Hajimolana, Sayed Ahmad; Hussain, Mohd Azlan; Soroush, M.; Daud, Wan Mohd Ashri Wan; Chakrabarti, M.H. (Fuel Cells, 2012)
A mathematical model based on first principles is developed to study the effect of heat and electrochemical phenomena on a tubul solid oxide fuel cell (SOFC). The model accounts fordiffusion, inherent impedance, transport (momentum, heat and mass transfer) processes, internal reforming/shifting reaction, electrochemical processes, and potential losses (activation, concentration, and ohmic losses). Thermal radiation of fuel gaseous components is considered in detail in this work in contrast to other reported work in the literature. The effect of thermal radiation on SOFC performance is shown by comparing with a model without this factor. Simulation results indicate that at higher inlet fuel flow pressures and also larger SOFC lengths the effect of thermal radiation on SOFC temperature becomes more significant. In this study, the H2 and CO oxidation is also studied and the effect of CO oxidation on SOFC performance is reported. The results show that the model which accounts for the electrochemical reaction ofCO results in better SOFC performance than other reported models. This work also reveals that at low inlet fuel flow pressures the CO and H2 electrochemical reactions are competitive and significantly dependent on the CO/H2 ratio inside the triple phase boundary. Â© 2012 WILEY-VCH Verlag GmbH & Co. KGaA,Weinheim.